Contact allergy to oxidised geraniol may be over-represented in individuals with photocontact allergy to ketoprofen - Bruze, Magnus; Marmgren, Victoria; Zimerson, Erik; Antelmi, Annarita; Svedman, Cecilia; Mowitz, Martin (Contact Dermatitis, 2024)
Background: Simultaneous overrepresentations of contact allergies and photocontact allergies are common in individuals with photocontact allergy to ketoprofen. Aims: To investigate whether contact allergy to oxidised (ox.) geraniol, geraniol, geranial, neral and citral is overrepresented in individuals with photocontact allergy to ketoprofen. Methods: The contact allergy rates to ox. geraniol, geraniol, geranial, neral and citral in routinely patch tested dermatitis patients were compared with the corresponding rates in individuals with photocontact allergy to ketoprofen. Results: Allergic patch test reactions were noted to ox. geraniol 11% (n = 39, 5.8%), ox. geraniol 6% (n = 12, 1.8%), geraniol 6% (n = 2, 0.3%), geranial (n = 18, 2.7%), neral (n = 7, 1.0%) and citral (n = 15, 2.2%). In those four patients who were diagnosed with photocontact allergy to ketoprofen during the test period, a significant overrepresentation (p = 0.020) of simultaneous contact allergy to ox. geraniol 11% was demonstrated. Overrepresentation of simultaneous contact allergy to various combinations of ox. geraniol, ox. limonene and ox. linalool was also noted in ketoprofen-photoallergic patients. Conclusions: Contact allergy to ox. geraniol, geranial and citral is common in routinely tested dermatitis patients. There is an overrepresentation of simultaneous contact allergy to ox. geraniol, ox. limonene and ox. linalool in patients with photocontact allergy to ketoprofen.
Publisher Copyright: © 2023 The Authors. Contact Dermatitis published by John Wiley & Sons Ltd.
Keywords: allergic contact dermatitis; CAS # 106-24-1; CAS # 22071-15-4; delayed hypersensitivity; fragrance substances; oxidation; patch testing; photopatch testing; photosensitiser; terpenes